Prophylactic Antiepileptic Drug Use and Outcome in the Ethnic/Racial Variations of Intracerebral Hemorrhage Study. Issue 12 (December 2015) - Sheth, Kevin N.; Martini, Sharyl R.; Moomaw, Charles J.; Koch, Sebastian; Elkind, Mitchell S.V.; Sung, Gene; Kittner, Steven J.; Frankel, Michael; Rosand, Jonathan; Langefeld, Carl D.; Comeau, Mary E.; Waddy, Salina P.; et al.
Abstract : Background and Purpose—: The role of antiepileptic drug (AED) prophylaxis after intracerebral hemorrhage (ICH) remains unclear. This analysis describes prevalence of prophylactic AED use, as directed by treating clinicians, in a prospective ICH cohort and tests the hypothesis that it is associated with poor outcome. Methods—: Analysis included 744 patients with ICH enrolled in the Ethnic/Racial Variations of Intracerebral Hemorrhage (ERICH) study before November 2012. Baseline clinical characteristics and AED use were recorded in standardized fashion. ICH location and volume were recorded from baseline neuroimaging. We analyzed differences in patient characteristics by AED prophylaxis, and we used logistic regression to test whether AED prophylaxis was associated with poor outcome. The primary outcome was 3-month modified Rankin Scale score, with 4 to 6 considered poor outcome. Results—: AEDs were used for prophylaxis in 289 (39%) of the 744 subjects; of these, levetiracetam was used in 89%. Patients with lobar ICH, craniotomy, or larger hematomas were more likely to receive prophlyaxis. Although prophylactic AED use was associated with poor outcome in an unadjusted model (odds ratio, 1.40; 95% confidence interval, 1.04–1.88; P =0.03), this association was no longer significant after adjusting for clinical and demographic characteristics (odds ratio, 1.11; 95% confidence interval, 0.74–1.65; P =0.62). Conclusions—: We found no evidence that AED use (predominantly levetiracetam) is independently associated with poor outcome. A prospective study is required to assess for a more modest effect of AED use on outcome after ICH. Abstract : Supplemental Digital Content is available in the text.